Hydrogen Sulfide Promotes Adipocyte Differentiation, Hyperplasia, and Hypertrophy. (January 2023) - Verma, Richa; Fu, Ming; Yang, Guangdong; Wu, Lingyun; Wang, Rui
Abstract: Hydrogen sulfide (H2 S) is endogenously produced in adipocytes and fat tissues and stimulates adipogenesis. The integrated pathogenic effects of H2 S on the development of obesity and the underlying mechanisms, however, have been unclear. Here, we find that a decreased endogenous H2 S level lowered lipid accumulation in mouse adipocytes. Exogenous H2 S treatment significantly increased the adipogenesis of primary mouse preadipocytes after six days of adipogenic induction. In the early phase of adipogenesis, H2 S increased cell proliferation and prepared cells to go through hyperplasia. After H2 S treatment for ten days, preadipocytes exhibited significantly greater cell surface area and diameter, indicating cell hypertrophy. Although it stimulated lipid accumulation and adipogenesis, H2 S had no effect on lipolysis. With nutrition overload and high glucose/insulin incubation, H2 S further stimulated glucose consumption and deteriorated adipocyte hypertrophy. H2 S upregulated hyperplasia genes (CCAAT/enhancer-binding protein ( C/EBPβ ), cell division cycle 25 ( Cdc25 ), minichromosome maintenance 3 ( Mcm3 ), and cell division cycle 45 ( Cdc45 )) and cyclin-dependent kinase 2 protein (Cdk2), which regulates cell proliferation. H2 S also upregulated the insulin receptor β (Irβ)-activated mitogen-activated protein kinase (MAPK) and protein kinase B (Akt) pathways, leading to adipogenesis. In conclusion, H2 S increases adipocyte differentiation, hypertrophy, and hyperplasia, implying that it plays a pathogenic role in obesity disorder.